Determination of Critical Slip Surface in Loose Rock Slope Stability Analysis - Zulkifl Ahmed; Sumra Yousuf; Mahwish Zahra; Anum Aleha; Abid Latif; Tahir Sultan; Tanveer Ahmad Khan; Muhammad Yousaf Raza Taseer (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Determination of representative Critical Slip Surface (CSS) for loose rock slope is one of the most important topics for slope reinforcement design. In this paper, a SLOPE/W software is used to analyze the failure characteristics of CSS considering the spatial variability effect of strength parameters. Initially, the Morgenstern-Price limiting equilibrium method was selected within the framework of SLOPE/W software to examine the failure mechanism of CSS and the corresponding Factor of Safety (FS) for a loose rock slope comprised of two different materials. Also, the variability effect of shear strength parameters (cohesion, friction angle) on minimum FS, the maximum depth (D), sliding arc length (L), distribution range of slip surfaces and slip surface entry point distance (De) were investigated through software. The results showed that all slip surfaces are mostly parallel and the local failure can happen at the top of the slope. Statistically, local failure has entry and exit points situated at the crest and near the toe of the slope, respectively. Shear strength parameters have a remarkable effect on FS, D, L and De of critical slip surface. The distribution range of CSS decreased with an increasing the amount of cohesion and friction angle. These findings can help to locate the actual position of CSS and slip surface entry point distance in case of loose rock slope.